Prevalence and Characteristics of Blood Pressure Phenotypes in Patients with Hypertension and Chronic Respiratory Diseases (Study of Ambulatory Practice Data of a Cardiologist) - A. S. Kurekhyan; M. I. Smirnova; V. M. Gorbunov; Ya. N. Koshelyaevskaya; A. D. Deev; M. M. Loukianov (Рациональная фармакотерапия в кардиологии)
Diagnosis of the blood pressure (BP) phenotype is the most important indication for its ambulatory measurement because BP phenotype is associated with cardiovascular complications and death. The study of BP phenotypes is important for patients with hypertension (HT) and comorbidity, including asthma and chronic obstructive pulmonary disease (COPD). The combination of HT with these lower airway diseases (LAD) leads to the mutual influence of pathologies creates difficulties in the drugs choice and may affect BP phenotype in HT patients.Aim. To compare in the prospective investigation various characteristics of BP phenotype in HT patients considering LAD (asthma or COPD).Material and methods. The prospective cohort study of ambulatory patients with HT (n=156) was carried out. The part of these patients had asthma or COPD (n=69). The clinical measurements and 24-hour BP monitoring, spirometry, clinical and biochemical blood tests, standard examination were performed, initially and after 12 months. BP phenotype were determined by the ratio of clinical BP and ambulatory BP considering their threshold values. Standard statistical methods and multivariate analysis were used.Results. Patients with LAD had 2 times more often prognostically unfavorable phenotypes: ineffective antihypertensive therapy (AHT) 37.3% vs 15.7% and masked AHT inefficiency 7.5% vs 4.5%; white coat HT on treatment (WCH) and effective AHT were less common(29.9% vs 42.7%; 25.5% vs 37.1%, respectively, p 148 mm Hg (b=2.733, p=0.040), LAD (b=1.015, p=0.011), serum total cholesterol (b=0.350, p=0.043), degree of nighttime diastolic BP decrease (for 13.1-18.0% b=-2.130, p=0.004; for 18.1-24.0% b=-2.509, p=0.001). The factors associated with masked AHT inefficiency in comparison to effective AHT were heart rate in orthostasis >87 beats/min(b=3,512, p=0.006) and SBP in orthostasis 141-148 mm Hg (b=3.405, p=0.004).Conclusion. The prevalence of prognostically unfavorable BP phenotypes (ineffective AHT and masked AHT inefficiency) is two times higher in HT patients with LAD. The first is associated with LAD presence, sex, and serum cholesterol; both phenotypes interrelated with hemodynamic parameters including degree of nighttime diastolic BP decrease. We found no association between AHT and LAD therapy with the BP phenotypes in this study. However, larger works in this area are required, including analysis of outcomes in long-term prospective studies.